Interactions Between Severe Acute Respiratory Syndrome Coronavirus 2 Replication and Major Respiratory Viruses in Human Nasal Epithelium. (29th August 2022) - Pizzorno, Andrés; Padey, Blandine; Dulière, Victoria; Mouton, William; Oliva, Justine; Laurent, Emilie; Milesi, Cedrine; Lina, Bruno; Traversier, Aurelien; Julien, Thomas; Trouillet-Assant, Sophie; Rosa-Calatrava, Manuel; et al.
Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), along with extensive nonpharmacological interventions, have profoundly altered the epidemiology of major respiratory viruses. Some studies have described virus-virus interactions, particularly manifested by viral interference mechanisms at different scales. However, our knowledge of the interactions between SARS-CoV-2 and other respiratory viruses remains incomplete. Here, we studied the interactions between SARS-CoV-2 and several respiratory viruses (influenza, respiratory syncytial virus, human metapneumovirus, and human rhinovirus) in a reconstituted human epithelial airway model, exploring different scenarios affecting the sequence and timing of coinfections. We show that the virus type and sequence of infections are key factors in virus-virus interactions, the primary infection having a determinant role in the immune response to the secondary infection. Abstract : We show that the virus type and the sequence of infections are key parameters of virus-virus interactions, having the impact of primary infections on the regulation of the immune response a determinant role in the outcome of secondary infections.